Social Structure and Culture in the Study of Race and Urban Poverty: A Critical Analysis of Issues, Evidence and Policy Perspectives in Contemporary American Sociology - Planel, Niels (Sens public, 2018)
This essay proposes a critical analysis of issues, evidence and policy perspectives pertaining to social structure, culture and agency in the study of race and urban poverty in contemporary American sociology.